Optimal acquisition and aggregation of offshore wind power by multiterminal voltage-source HVDC. - Weixing Lu (IEEE Transactions on power delivery)
This paper addresses the exploitation of the offshore wind energy. A good example is in the shallow coastal waters around the Baltic Sea where there is high potential for wind turbines, located 10-30 km from the shore. The underwater transmission of power to shore has to be by cables. Therefore, DC transmission is required to avoid the large capacitive reactance currents of AC cables. This paper describes the optimal acquisition and aggregation of wind power by multiterminal high-voltage direct current based on sinusoidal pulse-width-modulated, three-phase voltage-source converters connected at their AC terminals to the wind turbine generators.